Aspect Analysis in Higher Order Thinking Skills on the Evaluation Instrument of Protist Topic for the Grade 10 Senior Highschool Students - Riri Rahmadani Putri; Yuni Ahda; Rahmawati D (BIODIK, 2018)
Higher order thinking skills are essential for student future. The 2013 Curriculum demands the existence of an evaluation instrument to train student higher order thinking, not only the thinking skill in the lower cognitive domain, but also in a higher domain. One of the efforts to enhance higher order thinking skills is to engage students with the questions integrated by cognitive C4-C6. This study analysed aspects of higher order thinking in an evaluation instrument. This study used descriptive method by collecting evaluation instrument data used by teachers to evaluate a learning process. Evaluation instruments used by teachers at schools are still in the C1-C3 cognitive level (C1 47%, C2 47%, and C3 6%), the evaluation instruments are not eligible according to the standard applied. The skills demanded by the Fundamental Competency of the 2013 Curriculum. Higher order thinking skills of students are still relatively low, with the percentage mean of 52.03%. The low cognitive level obtained in the evaluation instrument used by the teachers is the reason of the low thinking level of the students.